Character Strengthening Through the Local Wisdom of Wailaki Kema Sa'o in Ende Ethnic Society - Suratih Muhamad Karo; Eny Kusdarini (International Journal of Social Science and Humanity, 2026)
This study aims to analyze the values of the local wisdom of Wailaki Kema Sa’o in house construction as an effort to strengthen the sense of responsibility and social concern among the community of Rukuramba Village, East Nusa Tenggara, as well as to identify the factors that support and hinder its implementation. The study employs a qualitative method with an ethnographic approach. Data were collected through observation, interviews, and documentation, and then analyzed using the Miles, Huberman, and Saldana model, which includes data condensation, data presentation, and drawing conclusions. The results of the study indicate that the Wailaki Kema Sa’o tradition embodies religious, aesthetic, cooperative, moral, and tolerant values that contribute to strengthening the character of responsibility and social concern among the community. The strengthening of a responsible character is reflected in responsibility toward duties, family, community, nation, and the environment, while a socially caring character is manifested through attitudes of mutual aid, empathy, tolerance, social action, and noble ethics. Supporting factors for the implementation of this tradition include the availability of facilities and infrastructure, community participation, community awareness, and support from the village government. The inhibiting factors are economic limitations and the declining involvement of the younger generation.